2021
DOI: 10.1039/d1nj02018h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient absorption of ammonia with dialkylphosphate-based ionic liquids

Abstract: Ammonia (NH3) absorption has attracted much attention due to serious environmental pollution caused by ammonia in recent years. In this paper, solubilities of ammonia (pressure-temperature-composition (pTx) data) in five dialkylphosphate-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Meanwhile, thermodynamic properties such as enthalpies, Gibbs free energies, entropies, and heat capacities were calculated for corresponding NH 3 + ILs mixtures, with the result of positive Δ sol G or negative Δ sol S , indicating that the absorbing process is nonspontaneous. Yu et al 82 designed five dialkylphosphate-based ILs of [C 4 C 1 im][DBP], [C 4 C 1 im][DMP], [C 2 C 1 im][DEP], [C 2 C 1 im][DMP] and [C 1 C 1 im][DMP] as suitable NH 3 absorbents. The solubilities of NH 3 in these ILs were determined at different temperatures (303.15–333.15 K) and pressures (0.1–0.6 MPa).…”
Section: Ionic Liquids For Nh3 Absorptionmentioning
confidence: 99%
“…Meanwhile, thermodynamic properties such as enthalpies, Gibbs free energies, entropies, and heat capacities were calculated for corresponding NH 3 + ILs mixtures, with the result of positive Δ sol G or negative Δ sol S , indicating that the absorbing process is nonspontaneous. Yu et al 82 designed five dialkylphosphate-based ILs of [C 4 C 1 im][DBP], [C 4 C 1 im][DMP], [C 2 C 1 im][DEP], [C 2 C 1 im][DMP] and [C 1 C 1 im][DMP] as suitable NH 3 absorbents. The solubilities of NH 3 in these ILs were determined at different temperatures (303.15–333.15 K) and pressures (0.1–0.6 MPa).…”
Section: Ionic Liquids For Nh3 Absorptionmentioning
confidence: 99%
“…Table summarizes the functional types and NH 3 absorption capacities of representative ILs reported in the literature. The process simulations performed by Zhan et al and Liu et al demonstrated that the IL-based NH 3 separation process exhibits significantly reduced energy consumption, operation cost, and net CO 2 emission than an aqueous-based process. , However, it should be pointed out that most ILs are expensive because they are normally synthesized from expensive reactants or through complicated routes. In addition, most ILs are with high viscosity due to the strong electrostatic attraction between cations and anions .…”
Section: Liquid Absorptionmentioning
confidence: 99%